LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK PROBLEM SOLVING UNTUK MENINGKATKAN PERENCANAAN KARIER SISWA DI SMA NEGERI 1 RONGGA - Khoerunida, Hawaidah; Eti Rohaeti, Euis; Agustine, Tiara (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
The aim of this research is to examine how students at SMA Negeri 1 Rongga prepare for their careers by using group guidance and problem solving techniques. The method used is Mixed Methods with the Explanatory Sequential Design design. The data obtained was normally distributed and homogeneous, then data analysis was carried out using parametric statistics via the t-test. The results of the t test and N-Gain test in the experimental group show that the significance value is 0.000. The significance value is less than a = 0.5, indicating that there is a significant difference between the pretest and posttest data from the experimental group. This shows that high school students' career planning using group guidance and problem solving techniques produces effective results.